Evaluating the Impact of a Flipped, a Traditional, and an Online Course on Grammar Knowledge Development and Content Coverage: Flipped Class’s Perception in Focus - Ahmad Khalifeh; Mohammad Bavali; Ehsan Rassaei (Journal of Modern Research in English Language Studies)
The integration of technology into education has offered new opportunities for higher education students. Flipped class, as part of this opportunity, has inspired ample research recently. However, there is still controversy over its effectiveness. To shed more light on its potentials, the present study compares a flipped class with a traditional and an online course in terms of their effects on developing the grammar knowledge of Iranian pre-intermediate TEFL students. In addition, the perceptions of the flipped group toward their learning experience in four areas were examined: motivation, effectiveness, interaction, and satisfaction. Finally, the potential of the flipped class to assist the instructor in presenting more topics was evaluated. Fifty-nine freshmen in two different classes were selected. Then, each class was randomly assigned to an experimental (n=31) or a control group (n=28). The former received instruction in a flipped class, whereas the latter attended a traditional class. Afterward, their performance was compared with that of another group attending an online course (n= 25). The data were collected through a timed and an untimed grammaticality judgment test and a perception scale. In order to compare the content coverage in the three classes, the number of units taught in each class was divided by the total number of units assigned for the semester. The results showed that instruction in the flipped class was as effective as instruction in the traditional class and both were more effective than the fully online course. Additionally, the flipped class seemed to be a satisfactory experience for the learners. The results also indicated that drawing on a flipped class can allow the instructor to present more content without compromising the quality of instruction and learning. The results can encourage language teachers, program developers, and educational policymakers to consider the flipped classroom as an acceptable alternative.